Prognostic factors for disability claim duration due to musculoskeletal symptoms among self-employed persons - Richter JM; Blatter BM; Heinrich J; de Vroome EMM; Anema JR (BMC, 2011)
Abstract Background Employees and self-employed persons have, among others, different personal characteristics and different working conditions, which may influence the prognosis of sick leave and the duration of a disability claim. The purpose of the current study is to identify prognostic factors for the duration of a disability claim due to non-specific musculoskeletal disorders (MSD) among self-employed persons in the Netherlands. Methods The study population consisted of 276 self-employed persons, who all had a disability claim episode due to MSD with at least 75% work disability. The study was a cohort study with a follow-up period of 12 months. At baseline, participants filled in a questionnaire with possible individual, work-related and disease-related prognostic factors. Results The following prognostic factors significantly increased claim duration: age > 40 years (Hazard Ratio 0.54), no similar symptoms in the past (HR 0.46), having long-lasting symptoms of more than six months (HR 0.60), self-predicted return to work within more than one month or never (HR 0.24) and job dissatisfaction (HR 0.54). Conclusions The prognostic factors we found indicate that for self-employed persons, the duration of a disability claim not only depends on the (history of) impairment of the insured, but also on age, self-predicted return to work and job satisfaction.